Conductive paste and conductive pattern using same

By using conductive paste with silver-clad copper sheets and silver-clad silica powder, the line width variation and insufficient conductivity of the conductive pattern during the printing process are solved, and high-precision and high-conductivity conductive pattern manufacturing is achieved.

JP7628530B2Active Publication Date: 2025-02-10TOYO ALUMINIUM KK

Patent Information

Application Number
JP2022505866
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-11
Filing Date
2021-02-16
Publication Date
2025-02-10
Estimated Expiration
2041-02-16

AI Technical Summary

Technical Problem

The existing conductive pastes are prone to linewidth variations and short circuits during printing, and the conductive patterns are insufficient in conductivity and migration resistance, making it difficult to meet the needs of high-precision and high-density circuits.

Method used

Silver-clad copper sheets and silver-clad silica powder are used as conductive powders, and combined with adhesives and solvents, the viscosity and fluidity of the conductive paste are adjusted to form a conductive pattern suitable for high-precision printing.

Benefits of technology

It realizes high-precision printing of conductive patterns, good line width stability, strong conductivity and migration resistance, and is suitable for high-density circuit manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628530000003
    Figure 0007628530000003
  • Figure 0007628530000004
    Figure 0007628530000004
  • Figure 0007628530000005
    Figure 0007628530000005
Patent Text Reader

Abstract

The purpose of the present invention is to provide: an electroconductive paste which is capable of printing an electroconductive pattern with high accuracy, said electroconductive pattern being suppressed in variation in the line width, and which enables the printed electroconductive pattern to have high electrical conductivity, high thermal conductivity, high migration resistance and the like; and an electroconductive pattern which uses this electroconductive paste. The present invention provides: an electroconductive paste containing silver-coated copper flakes and a silver-coated silica powder, said electroconductive paste being obtained by adding a silver-coated silica powder to silver-coated copper flakes serving as a base material; and an electroconductive pattern which uses this electroconductive paste. In addition, this electroconductive paste may additionally contain a binder resin, a solvent and a curing agent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive paste used for forming a conductive pattern such as an electrode of an electronic device, and a conductive pattern using the same. [Background technology]

[0002] Conductive pastes are used for a variety of purposes, such as mounting and fixing semiconductor elements (semiconductor chips) such as ICs and LSIs onto metal pieces called lead frames, forming circuits on substrates by printing or other methods, and forming electrodes for electronic components such as capacitors.

[0003] Furthermore, with the recent increase in the degree of integration of semiconductor chips and the increasing density of circuits on circuit boards, there is a demand for conductive pastes that have little variation in line width and enable circuit patterns to be printed with high precision, and that the printed circuit patterns have high electrical conductivity and thermal conductivity, high migration resistance, and excellent workability due to their appropriate viscosity and fluidity.

[0004] For example, JP 2012-18783 A (Patent Document 1) discloses a conductive paste that can form conductive film wiring with low volume resistivity and has improved adhesion to substrates and printability by adding fine silver particles with an average primary particle diameter of 10 nm or more and 200 nm or less to silver particles with an average particle diameter of 0.5 μm or more to suppress a decrease in the fluidity of the conductive paste.

[0005] In addition, JP 2019-102273 A (Patent Document 2) discloses a conductive paste that suppresses viscosity reduction by using three types of fillers including nanoparticles so that the paste has an appropriate viscosity to maintain a thin line shape while maintaining low electrical resistance.

[0006] However, in the conductive pastes described in Patent Documents 1 and 2, it is difficult to disperse nano-sized fillers, and the fluidity tends to be high. If the fluidity is too high, the conductive paste will bleed after printing, causing variations in line width, which can result in short circuits. In addition, there is also a problem that the conductive patterns formed using these conductive pastes do not necessarily have high migration resistance.

[0007] In addition, conductive powders such as silver particles become more difficult to disperse when the loading amount is large. Therefore, compositions highly loaded with conventional flaky (or flat) silver powder or spherical silver powder, etc., are prone to poor appearance and have problems such as reduced adhesive strength and workability. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2012-18783 A [Patent Document 2] JP 2019-102273 A Summary of the Invention [Problem to be solved by the invention]

[0009] Therefore, an object of the present invention is to provide a conductive paste which has little variation in line width and enables printing of a conductive pattern with high precision, and in which the printed conductive pattern has high electrical conductivity and high migration resistance, and which has suitable viscosity and fluidity and thus excellent workability, and a conductive pattern (circuit pattern) using the same. [Means for solving the problem]

[0010] In view of the above problems, the inventors conducted extensive research into the types, shapes, and combinations of conductive powders that are effective in suppressing line width variations and migration caused by bleeding during printing and that achieve high electrical conductivity and excellent workability. As a result, they discovered that the above problems can be solved by using silver-coated copper flakes as a base for a conductive paste to which silver-coated silica powder is added, thereby completing the present invention.

[0011] That is, according to the present invention, there is provided a conductive paste containing silver-coated copper flakes and silver-coated silica powder, and a conductive pattern using the same. The conductive paste of the present invention may further contain a binder resin, a solvent, and a hardener.

[0012] The conductive paste of the present invention is a composition formed into a paste by adding silver-coated copper flakes, silver-coated silica powder, and a binder resin to the above. As long as the paste contains silver-coated copper flakes, silver-coated silica powder, and a binder resin, it may contain other components such as a solvent and an antifoaming agent as necessary within a range that does not impair the effects of the present invention.

[0013] The silver-coated copper flakes used in the present invention are not particularly limited, and any known flake-shaped copper powder coated with silver can be used. The volume average particle diameter (D 50 The volume average particle diameter (D) of the silver-coated copper flakes is preferably 1.0 μm or more and 50 μm or less, and more preferably 2.0 μm or more and 20 μm or less. 50 ) is 2.0 μm or more and 20.0 μm or less, it becomes extremely easy to deal with thin lines when drawing a circuit. Note that, although spherical or nearly spherical copper powder or flake-shaped copper powder is known as the copper powder to be coated with silver, it is preferable to use silver-coated copper flakes in the present invention from the viewpoint of suppressing the decrease in electrical contacts after the circuit is formed and suppressing the increase in electrical resistance.

[0014] The silver-coated copper flakes may be completely coated with silver, or may have some copper exposed. Being completely coated with silver is preferable because it reduces the resistivity. The amount of silver-coated copper flakes is preferably 10% by volume or more and 40% by volume or less, and more preferably 30% by volume or more and 40% by volume or less, based on the total non-volatile content of the conductive paste. If the amount of silver-coated copper flakes is 10% by volume or more and 40% by volume or less, it is possible to improve workability by having appropriate viscosity and fluidity while keeping the resistivity low.

[0015] The silver-coated silica powder used in the present invention is not particularly limited as long as it is a silica powder coated with silver, and any known powder can be used. The volume average particle diameter (D 50 The volume average particle diameter (D) of the silver-coated silica powder is preferably 0.050 μm or more and 50.0 μm or less, and more preferably 0.1 μm or more and 5.0 μm or less. 50 If the diameter is 0.1 μm or more and 5.0 μm or less, a high filling rate can be achieved, thereby making it possible to keep the resistivity low.

[0016] The silver-coated silica powder may be completely coated with silver, or may have a part of the silica exposed. Completely coated with silver is preferable because it reduces the specific resistance. The amount of silver-coated silica powder is preferably in the range of 99:1 to 15:85 in terms of the volume ratio of silver-coated copper flakes to silver-coated silica powder, and more preferably in the range of 99:1 to 20:80.

[0017] If the volume ratio of silver-coated copper flakes to silver-coated silica powder is in the range of 99:1 to 15:85, the fluidity of the obtained conductive paste is particularly favorable, and the variation in lines when printed is reduced, and the electrical conductivity and migration resistance of the formed circuit pattern are also improved. In addition, the shape of the silver-coated silica powder is not particularly limited as long as it is particulate. Particulate form is particularly favorable because it has excellent fluidity.

[0018] In addition, in this specification, numerical (ratio) ranges indicated using "from" or "to" indicate ranges that include the numerical (ratio) values ​​written before and after "from" or "to" as the minimum value (ratio) and maximum value (ratio), respectively.

[0019] The binder resin used in the present invention is not particularly limited and any known resin can be used. Thermosetting resins include epoxy resins, phenolic resins, urea resins, unsaturated polyester resins, alkyd resins, polyurethanes, and thermosetting polyimides. Thermoplastic resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyester, and polyamide having functional groups remaining at the terminals may also be used in combination with a curing agent.

[0020] In order to achieve workability and printability suitable for various printing methods such as screen printing, it is preferable to mix the resin binder at a ratio of 30 volume % to 60 volume % of the total non-volatile content of the conductive paste.

[0021] The solvent used in the conductive paste of the present invention is not particularly limited. It can be appropriately selected depending on the solubility of the resin used and the type of printing method. Examples of the solvent of the present invention include ester solvents, ketone solvents, glycol ether solvents, aliphatic solvents, alicyclic solvents, aromatic solvents, alcohol solvents, water, and the like, or a mixture of two or more of them.

[0022] Examples of ester-based solvents include ethyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, amyl acetate, ethyl lactate, and dimethyl carbonate. Examples of ketone-based solvents include acetone, methyl ethyl ketone, methyl isobutyl ketone benzene, diisobutyl ketone, diacetone alcohol, isophorone, and cyclohexanenone. Examples of glycol ether-based solvents include ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, and acetate esters of these monoethers, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and acetate esters of these monoethers.

[0023] On the other hand, examples of aliphatic solvents include n-heptane, n-hexane, isohexane, isoheptane, etc. Examples of alicyclic solvents include methylcyclohexane, ethylcyclohexane, cyclohexane, etc. Examples of aromatic solvents include toluene, xylene, tetralin, etc. Examples of alcohol solvents (excluding the above-mentioned glycol ether solvents) include ethanol, propanol, butanol, etc.

[0024] Furthermore, in a circuit pattern in which multiple straight lines are printed on a PET resin sheet with intervals of approximately 100 μm using the conductive paste of the present invention described above, adjacent lines do not short circuit (contact) with each other due to small variation in line width, and a circuit pattern can be obtained in which each line has excellent electrical conductivity. Effect of the Invention

[0025] The conductive paste of the present invention has an appropriate viscosity and an appropriate fluidity, and therefore has excellent workability, and exhibits the excellent effect of enabling circuit patterns to be printed with high precision with little variation in line width. The conductive paste also exhibits the excellent effect of having high electrical conductivity and high migration resistance in the printed conductive pattern. [Brief description of the drawings]

[0026] [Figure 1] 1 is a micrograph of a circuit pattern (conductive pattern) printed using the conductive paste of Example 4. [Diagram 2] 1 is a micrograph of a circuit pattern (conductive pattern) printed using the conductive paste of Comparative Example 1. [Diagram 3] 1 is a micrograph of a circuit pattern (conductive pattern) printed using the conductive paste of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, a conductive paste according to an embodiment of the present invention and a conductive pattern using the same will be described in detail with reference to the drawings. Note that the present invention is not limited to the following examples, and various modifications are possible within the scope of the technical concept of the present invention. EXAMPLES

[0028] 1. Preparation of Conductive Paste The conductive paste according to one embodiment of the present invention and the conductive paste of the comparative example were produced using the following materials and under the following conditions (see Table 1). [Example 1] The volume average particle diameter (D 50 65.1 g of Toyal Tech Filler (registered trademark) / TFM-C05F (manufactured by Toyo Aluminum Co., Ltd.) with a volume average particle diameter (D ) of 6 μm was used as silver-coated silica powder. 50The conductive paste of Example 1 was produced by mixing 0.29 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a particle size of 2 μm, 12.0 g of Elitel (registered trademark) / UE-3210 (manufactured by Unitika Co., Ltd.) as a binder resin, 1.7 g of blocked isocyanate (product name: 7992, manufactured by Baxenden Co., Ltd.) as a curing agent, and 24.9 g of a mixed solvent of ethyl carbitol acetate and isophorone in a weight ratio of 16:9 as a solvent, and kneading using a disper and a three-roll mill.

[0029] [Example 2] The volume average particle diameter (D 50 The conductive paste of Example 2 was produced under the same conditions as Example 1, except that 0.57 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) having a particle size of 2 μm was added.

[0030] [Example 3] The volume average particle diameter (D 50 The conductive paste of Example 3 was produced under the same conditions as Example 1, except that 1.2 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) having a particle size of 2 μm was added.

[0031] [Example 4] The volume average particle diameter (D 50 The conductive paste of Example 4 was produced under the same conditions as Example 1, except that 2.3 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) having a particle size of 2 μm was added.

[0032] [Example 5] The volume average particle diameter (D 50 25.9 g of Toyal Tech Filler (registered trademark) / TFM-C05F (manufactured by Toyo Aluminum Co., Ltd.) with a volume average particle diameter (D ) of 6 μm was used as silver-coated silica powder. 50The conductive paste of Example 5 was produced under the same conditions as Example 1, except that 32.3 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) having a particle size of 2 μm was added.

[0033] [Comparative Example 1] A conductive paste of Comparative Example 1 was produced under the same conditions as in Example 1, except that the silver-coated silica powder was not added.

[0034] [Comparative Example 2] Without the use of silver-coated copper flakes, the volume average particle diameter (D 50 The conductive paste of Comparative Example 2 was produced under the same conditions as in Example 1, except that 47.9 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) having a particle size of 2 μm was blended.

[0035] [Comparative Example 3] Without the use of silver-coated copper flakes, the volume average particle diameter (D 50 The conductive paste of Comparative Example 3 was produced under the same conditions as in Example 1, except that 7.9 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) having a particle size of 2 μm was added.

[0036] [Comparative Example 4] As an alternative to silver-coated silica powder, the volume average particle size (D 50 The conductive paste of Comparative Example 4 was produced under the same conditions as in Example 1, except that 2.3 g of spherical silver powder (product name: HXR-Ag, manufactured by Nippon Atomize Processing Co., Ltd.) having a diameter of 5.7 μm was added.

[0037] [Comparative Example 5] As an alternative to silver-coated copper flakes, 50 65.1 g of silver flakes (product name: TCG-1, manufactured by Tokuriki Chemical Laboratory Co., Ltd.) with a volume average particle diameter (D 50The conductive paste of Comparative Example 5 was produced under the same conditions as in Example 1, except that 2.3 g of Toyal Tech Filler (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) having a particle size of 2 μm was added.

[0038] [Comparative Example 6] As an alternative to silver-coated copper flakes, 50 The conductive paste of Comparative Example 6 was produced under the same conditions as in Example 1, except that 65.1 g of 4.8 μm silver flakes (product name: TCG-1, manufactured by Tokuriki Chemical Laboratory Co., Ltd.) was added and no silver-coated silica powder was added.

[0039] Table 1 shows the amount (g) of each component added to the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6, and the blending ratio (Vol %) of each component relative to the total non-volatile content of the conductive paste. [Table 1]

[0040] 2. Creation of circuit patterns (conductive patterns) Using the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6, a screen plate made of stainless steel, with a screen mesh number of 325 meshes, an emulsion thickness of 10 μm, a line width of 100 μm, and a line interval of 100 μm was used to print on a PET resin sheet with a screen printer (product name: DP-320 type screen printer, manufactured by Newlong Precision Industry Co., Ltd.). Then, the sheet on which the circuit pattern was printed was dried at 150° C. for 30 minutes to prepare a circuit pattern for evaluation.

[0041] 3.Evaluation of conductive paste and circuit patterns (1) Viscosity To investigate the relationship between the workability and spreading of the conductive paste, the viscosity of the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 was measured at a temperature of 25° C. and a rotation speed of 0.5 rpm using a Brookfield type viscometer (model number: DV2THBCJ0). The results are shown in Table 2.

[0042] (2) Variation in line width The above-mentioned evaluation circuit patterns made using the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 were observed at a magnification of 50 times using an inspection microscope (product name: ECLIPSE L200, manufactured by Nikon Corporation), and images were taken. The obtained images were then binarized using image analysis software (product name: Winroof 2018, manufactured by Mitani Shoji Co., Ltd.). The line widths of 1,000 points were measured from the binarized images, and the 3σ value, which is an index of the variation in line width, was obtained. 3σ means an interval three times the standard deviation (σ), and in the case of normal distribution, approximately 99.7% of the samples fall within the range of the average value ±3σ.

[0043] The smaller the 3σ value of the line width variation of the circuit pattern, the better, but if the 3σ value exceeds 50 μm, adjacent lines may short-circuit when current is applied, and so it is rated as "×" (bad), and if it is 50 μm or less, it is rated as "◯" (good). Also, if a short circuit (contact) was observed between some of the adjacent lines from the beginning of the circuit pattern formation, it was rated as "×" (bad) regardless of the 3σ value. The above results are shown in Table 2.

[0044] Of the above-mentioned evaluation circuit patterns, a micrograph of the circuit pattern produced using the conductive paste of Example 4 is shown in FIG. 1, a micrograph of the circuit pattern produced using the conductive paste of Comparative Example 1 is shown in FIG. 2, and a micrograph of the circuit pattern produced using the conductive paste of Comparative Example 3 is shown in FIG. 3.

[0045] (3) Migration resistance The migration resistance of the circuit patterns was evaluated by measuring the time until a short circuit occurred while each of the above-mentioned evaluation circuit patterns was kept under the conditions of 85°C, 85% humidity, and an applied voltage of 50 V. The presence or absence of a short circuit in the circuit patterns was confirmed using a migration tester (product name: MODEL MIG-87B, manufactured by IMV Corporation).

[0046] In this embodiment, a time period until a short circuit occurs was 800 hours or more and a time period until a short circuit occurs was evaluated as "◯" (good), and a time period less than 800 hours was evaluated as "×" (bad). The results are shown in Table 2.

[0047] (4) Resistivity The resistivity value (Ω·cm) of the circuit pattern was measured by printing the conductive paste on a PET film using a screen plate for evaluation made of polyester resin, 280 mesh screen, and 9 micron emulsion thickness in a square shape of 4.8 cm x 4.8 cm, and then drying the conductive paste at 150°C for 30 minutes to form a coating film. The thickness of the coating film was confirmed by measuring with a Digimatic Standard Outside Micrometer (product name: IP65 COOLANT PROOF Micrometer, manufactured by Mitutoyo Corporation). It was also confirmed by measuring with a four-probe surface resistance meter (product name: Loresta GP, manufactured by Mitsubishi Analytec Corporation). For each evaluation circuit pattern, five arbitrary points were measured, and the average value was used as the resistivity value. Specifically, the dimensions of the printed matter, the average thickness of the printed matter, and the coordinates of the measurement points were input into the four-probe surface resistance meter, and the value obtained by automatically calculating the value was used as the resistivity value of the conductive layer (circuit pattern / conductive pattern).

[0048] The smaller the resistivity value, the better the electrical conductivity. The dimensions of the printed matter refer to the maximum length and maximum width of the pattern of a given shape that the printed matter has. The smaller the resistivity value, the better the electrical conductivity. -4 If the resistance is less than Ω·cm, it is evaluated as "good" (good). Conversely, if the resistance is less than 2.0×10 -4 If the resistance was greater than Ω·cm, it was evaluated as "×" (failure). The results are shown in Table 2.

[0049] The overall evaluation of each evaluation circuit pattern was given a rating of "Good" (O) only if it received a rating of "O" in all of the above-mentioned evaluations of "Line width variation," "Migration resistance," and "Specific resistance value." If there was even one rating of "X" in any of the individual evaluations, the overall evaluation was also given a rating of "X" (Bad).

[0050] Table 2 shows the evaluation results of the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 and the circuit patterns (conductive patterns) produced using them. [Table 2]

[0051] 4. Discussion Comparing the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 from Table 2, it was found that the conductive paste of the present invention is based on silver-coated copper flakes to which silver-coated silica powder is added, and thereby good results can be obtained in the evaluations of "line width variation," "migration resistance," and "specific resistance value" of the printed circuit pattern (conductive pattern). As a result, it is possible to print conductive patterns with little line width variation and with high precision. Furthermore, the printed conductive patterns have high electrical conductivity and thermal conductivity, high migration resistance, and excellent workability due to their viscosity of 30 Pa·s or more and 70 Pa·s or less.

[0052] In particular, by comparing the conductive pastes of Examples 1 to 5 with the conductive pastes of Comparative Examples 1 to 3, it was found that when the volume ratio of silver-coated copper flakes to silver-coated silica powder is preferably in the range of 99:1 to 15:85, and more preferably in the range of 99:1 to 20:80, the printed circuit pattern has small line width variations and excellent migration resistance and conductivity can be obtained, and further, when the volume ratio of silver-coated copper flakes to silver-coated silica powder is in the range of 99:1 to 90:10, as in the conductive pastes of Examples 1 to 4, even better migration resistance can be obtained.

[0053] In addition, the conductive pastes of Examples 1 to 5 have a silver-coated copper flake content of 10% by volume or more and 40% by volume or less based on the total non-volatile content of the conductive paste, so that the printed circuit pattern has a small variation in line width, excellent migration resistance and conductivity, and has a suitable viscosity and fluidity while keeping the specific resistance low, thereby improving workability. Furthermore, it was found that, as in the conductive pastes of Examples 1 to 4, the silver-coated copper flake content of 30% by volume or more and 40% by volume or less based on the total non-volatile content of the conductive paste can provide even better migration resistance.

[0054] Furthermore, in the conductive pastes of Examples 1 to 5, it was found that it is effective to mix a resin binder in a ratio of 30 volume % or more and 60 volume % or less with respect to the total non-volatile content of the conductive paste in order to achieve workability and printability suitable for various printing methods such as screen printing.

[0055] The conductive pastes of Examples 1 to 5 have a volume average particle diameter (D 50 It has been found that when the thickness of the ink is preferably 1.0 μm or more and 50 μm or less, and more preferably 2.0 μm or more and 20 μm or less, the printed circuit pattern has little variation in line width, and it is extremely easy to deal with thin lines when drawing the circuit pattern.

[0056] In addition, the conductive pastes of Examples 1 to 5 have a volume average particle diameter (D 50 It has been found that when the thickness of the conductive layer is preferably 0.050 μm or more and 50.0 μm or less, and more preferably 0.1 μm or more and 5.0 μm or less, a high filling rate is achieved, thereby keeping the resistivity low and reducing the variation in line width in the printed circuit pattern.

[0057] Furthermore, from Figures 1 to 3, it was found that a circuit pattern (conductive pattern) in which multiple lines are printed at intervals of about 100 μm using the conductive paste of the present invention has small variation in line width, so that adjacent lines do not short-circuit (contact) with each other, and a circuit pattern with excellent electrical conductivity of each line can be obtained. [Explanation of symbols]

[0058] L...Print line G···Gap (PET resin sheet) S... Short circuit part (contact part)

Claims

1. The present invention includes a silver-coated copper flake and a silver-coated silica powder. The average particle size of the silver-coated copper flakes is 2.0 μm or more and 20.0 μm or less, and The conductive paste is characterized in that the average particle size of the silver-coated silica powder is 0.1 μm or more and 5.0 μm or less.

2. 2. The conductive paste according to claim 1, wherein a mixing ratio of the silver-coated copper flakes to the silver-coated silica powder is within a range of 99:1 to 15:85 in volume ratio.

3. 3. The conductive paste according to claim 1, further comprising a resin binder in an amount of 30% by volume or more and 60% by volume or less based on the total non-volatile content of the conductive paste.

4. A conductive pattern formed by using the conductive paste according to claim 1 .

Citation Information

Patent Citations

  • Method for treating metal-coated particles

    JP2009533552A

  • Conductive paste

    JP2012018783A

  • Conductive resin composition and semiconductor device

    JP2015026519A

  • Manufacturing method of electric conductive paste and electric conductive paste

    JP2017050119A

  • Conductive paste composition

    JP2019102273A

Cited By

  • Conductive paste and solar cell including electrode composed of cured product thereof

    JP2023071376A